(untitled) (Journal of Parents and Teachers, 2014)
The theater is an artistic manifestation that allows to work with strategies of socialization, of resolution of conflicts, and of communication from a playful, pedagogic and motivational approach. The authors of the article show the capacity of education that the performing arts have, providing examples of works of didactic interest.